Erwerbspersonen- und Arbeitsvolumenprojektionen bis ins Jahr 2060 - Daniel Ehing; Stefan Moog (Journal for Labour Market Research, 2013)
– This paper analyzes the impact of demographic change on the labor force in Germany. First, to account for observable trends in labor force participation a cohort-component model is applied to project the future development of the labor force. Based on this trend scenario we assess the impact of several policy options to counteract the demographic decline in labor supply. The policy options analyzed include an increase in the effective retirement age, a decline in the age of labor market entry, an increasing labor force participation of the elderly, raising the labor force participation of immigrants as well as a further increase in female participation rates. Second, the effects of a declining unemployment rate as well as the effects of an increase in the hours worked are examined, focusing on the overall annual work volume. Our results suggest that the annual work volume can be stabilized sufficiently. Therefore future productivity gains do not have to be eroded substantially in order to maintain the GDP per capita level of the base year 2010.
Keywords: J11; J21; 330; Arbeitsmarktprognose; Arbeitsvolumen; Erwerbspersonenpotenzial; demografischer Wandel - Auswirkungen; Szenario; Arbeitskräftemangel; Erwerbsbeteiligung; Frauen; ältere Arbeitnehmer; ausländische Arbeitnehmer; Einwanderer; Arbeitszeitverlängerung; Beschäftigungseffekte; Erwerbslosenquote; Teilzeitarbeit; Bevölkerungsprognose; Lebensarbeitszeit